Community Based Medical Education: What, Why and How? - Nurunnabi, Abu Sadat Mohammad; Hasan, Mahmud Javed; Quddush, ASM Ruhul; Jahan, Shahanaz; Kaiser, Amir Mohammad; Afrose, Tanzina; Parveen, Shamima (Community Based Medical Journal, 2024)
Community based medical education has several definitions, but the core definition refers to learning that takes place is need based and in a community setting. Hence, community based medical education refers to medical education in which trainees learn and acquire professional competencies in a community setting based on the need of the community. This concept encourages medical colleges to produce not just highly competent professionals, but professionals who are equipped to respond to the changing challenges of healthcare through re-orientation of their education, research, and service commitments, and be capable of demonstrating a positive effect upon the communities they serve. Such social accountability of a healthcare cum academic institution demonstrates an impact on the communities served and thus, contribute to achieve a just and efficient healthcare service through mutually beneficial partnerships with other stakeholders. Community based medical education can make a difference in the country’s health sector by supporting a community based healthcare delivery system within the concept of National Health Policy and thus, contribute to the overall national efforts in achieving meaningful, self-sustaining quality of life and environment. Besides, it helps bring about change in current educational trait by imposing need-based, flexible academic strategies specific to the rural community and quality of the medical doctors by grooming them as empathetically responsive and active towards patients, professionally competent and ethically sound persons of the society. CBMJ 2024 January: vol. 13 no. 01 P: 119-129